1994
DOI: 10.1007/bf00192540
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal structure of protophloem sieve-element cell wall in colchicine-treated roots of Triticum aestivum L.

Abstract: The structural aberrations of the cell walls of protophloem sieve elements (PSEs) in roots of wheat (Triticum aestivum L. cv. Maris Huntsman) caused by the anti-microtubule drug colchicine were investigated by electron microscopy. The initial effect of the drug on cell wall development was found to be an exceptionally rough wall surface, presumably caused by an uncontrolled fusion of Golgi vesicles with the plasma membrane. Cellulose microfibrils, which in normal PSEs are aligned transversely to the long axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this study, however, no such disruption was observed at least at the light microscope level. Disruption of the cortical network of MTs in wheat roots with MT drugs is known to cause localized bulging of the cell wall (Eleftheriou 1994), although the mechanistic relationship of this cellular response to that producing wall ingrowth formation is unknown. Alternatively, the actin cytoskeleton is well known to be involved in establishing cellular polarity (Kropf 1992) and in transporting wall precursor-containing vesicles to sites of synthesis of plant cell walls (Steer and Steer 1989).…”
Section: Role Of Mts In the Construction Of Wall Ingrowthsmentioning
confidence: 99%
“…In this study, however, no such disruption was observed at least at the light microscope level. Disruption of the cortical network of MTs in wheat roots with MT drugs is known to cause localized bulging of the cell wall (Eleftheriou 1994), although the mechanistic relationship of this cellular response to that producing wall ingrowth formation is unknown. Alternatively, the actin cytoskeleton is well known to be involved in establishing cellular polarity (Kropf 1992) and in transporting wall precursor-containing vesicles to sites of synthesis of plant cell walls (Steer and Steer 1989).…”
Section: Role Of Mts In the Construction Of Wall Ingrowthsmentioning
confidence: 99%
“…During the differentiation of a number of plant cell types, including tracheary elements (Chaffey et al 2000), sieve elements (Eleftheriou 1994), guard cells (Apostolakos andGalatis 1998, 1999), and mesophyll cells (Jung and Wernicke 1990), localized thickenings of secondary-cell-wall material are deposited in specific patterns at the cell surface. These thickenings are deposited as extended ridges or bands that protrude into the cell, with cellulose microfibrils in these bands usually being parallel and laid down in an ordered pattern (Hepler 1981).…”
Section: Possible Mechanisms For Controlling the Spatial Aspects Of Wmentioning
confidence: 99%
“…The presumed effects of Cr(VI) on plant hormones and the correlation of changed MT orientation with the cellulose alignment in Cr(VI)-treated cells raise additional interesting questions for further investigation. Such a change of cellulose microfibril alignment from perpendicular to longitudinal was revealed by electron microscopy in differentiating protophloem sieve elements of wheat treated with colchicine which depolymerizes MTs (Eleftheriou 1994), indicating that besides MTs other regulating mechanisms may be activated in cells under stress. Correlation of MT bundling with α-tubulin acetylation Acetylation of α-tubulin is a post-translational modification first discovered in stable MT structures, notably axonemes from a variety of sources (Piperno and Fuller 1985;LeDizet and Piperno 1987), and further on in subsets of more labile MT frameworks such as cytoplasmic MTs and mitotic spindles LeDizet and Piperno 1991).…”
Section: Universality Of Microtubule Disruption By Cr(vi)mentioning
confidence: 97%